TEKNOLOGI DAN INOVASI DALAM PENGENDALIAN MUTU PENDIDIKAN SERTA PERAN PEMIMPIN LEMBAGA DAN GURU DI SDN BOGAK TAHUN PELAJARAN 2026/2027 - Suryajaya; Lalu Andi Fathullah; Mardiana; Basilius Redan Werang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the utilization of technology and innovation in educational quality control and to examine the roles of the principal and teachers at SDN Bogak during the 2026/2027 academic year. The research employed a descriptive qualitative approach, with data collected through observations, semi-structured interviews, and documentation. The participants included the principal, teachers, administrative staff, students, and parents or guardians. Data were analyzed using the processes of data condensation, data display, and conclusion drawing and verification. Administratively, the school is supported by 11 personnel, consisting of 9 teachers (2 civil servant teachers, 5 full-time government contract teachers, and 2 part-time government contract teachers), 1 school caretaker, and 1 cleaning staff member. The analytical framework positions technology as a strategic tool to support teaching and learning, assessment, data management, communication, supervision, and data-driven planning. The principal plays a key role in setting the school's strategic direction, ensuring the availability of technological infrastructure, developing staff competencies, and monitoring program implementation. Meanwhile, teachers are responsible for designing technology-enhanced learning, utilizing assessment data to improve instruction, and evaluating the impact of educational innovations on student learning outcomes. The findings suggest that technology-based quality control should be implemented gradually, focusing on students' needs while ensuring security, equity, and continuous evaluation to achieve sustainable educational improvement.